Analysis by RP-HPLC and Purification by RP-SPE of the C-Tetra(p-hydroxyphenyl)resorcinolarene Crown and Chair Stereoisomers - Alver A. Castillo-Aguirre; Zuly Jenny Rivera Monroy; Mauricio Maldonado (Journal of Analytical Methods in Chemistry)
A method for the separation of stereoisomer mixture of the octol C-tetra(p-hydroxyphenyl)calix[4]resorcinarene that was obtained by an acid cyclocondensation reaction between resorcinol and benzaldehyde is reported in this paper. A crude product from octol formation reaction was analyzed by reverse-phase high-performance liquid chromatography (RP-HPLC), and two well-resolved signals corresponding to the crown and chair isomers were found. A reverse phase in solid-phase extraction (RP-SPE) protocol allowed the separation of the two stereoisomers with high purity of each isomer. Finally, the crude and purified stereoisomers were characterized by using FT-IR, 1H-NMR, and 13C-NMR techniques, confirming the chemical identity of the two isomers and the efficiency in the separation process.